Evaluation of anti-epileptic property of Marsilea quadrifolia Linn. in maximal electroshock and pentylenetetrazole-induced rat models of epilepsy. (December 2013) - Snehunsu, Adhikari; Mukunda, N.; Satish Kumar, M. C.; Sadhana, Nandi; Naduvil Narayanan, Sareesh; Vijay Kapgal, K.; Avinash, H.; Chandrashekar, B. R.; Raghavendra Rao, K.; Nayak, B. Satheesha
Abstract Objective: To study the anti-epileptic effects of methanolic extract of Marsilea quadrifolia Linn. (MQ) in maximal electroshock (MES) and pentylenetetrazole (PTZ) induced rat models of epilepsy. Method: A total of 84 adult male Wistar rats were used. An acute oral toxicity study was conducted on 36 rats and the remaining were used for other experiments. Each model had 24 rats which were allotted into four groups (n = 6). Group I (Control) received 1% carboxymethyl cellulose solution, Group II (Positive control) received phenytoin 300 mg kg−1 b.w. in the MES model; sodium valproate 200 mg kg−1 b.w. in the PTZ model, Group III (MQ) received 400 mg kg−1 b.w. MQ extract and Group IV (MQ) received 600 mg kg−1 b.w. MQ extract. Hind limb extension (HLE) time and recovery time were noted in the MES model. Latency for myoclonic jerk, seizures and EEG was recorded in the PTZ model. Results: When compared to control, the phenytoin received group did not show HLE. In MQ pre-treated groups only 50% of rats showed HLE. Sodium valproate and various doses of MQ significantly increased the latency for onset of clonus and seizures. PTZ-induced EEG alterations were significantly attenuated by MQ administration and this was comparable to that of the sodium valproate effect. Conclusion: Marsilea quadrifolia Linn. showed significant anti-epileptic efficacy against various epilepsy models.